SAT0221 FACTORS AFFECTING MORTALITY OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS IN SPAIN IN THE 21ST CENTURY: DATA FROM THE RELESSER REGISTRY. (2nd June 2020) - Moriano, C.; Calvo, J.; Rua-Figueroa, I.; Diez Alvarez, E.; Bermúdez, C.; López-Longo, F. J.; Galindo-Izquierdo, M.; Olive, A.; Tomero Muriel, E.; Fernandez-Nebro, A.; Freire González, M.; Fernández-Berrizbeitia, O.; et al.
Abstract : Background: The mortality in Systemic Lupus Erythematosus (SLE) varies largely across different countries most probably due to social, healthcare and ethnic differences. Objectives: To analyze the causes and identify predictive factors of mortality of SLE in Spain in the present century. Methods: We performed a cross-sectional and retrospective study analyzing data from the RELESSER cohort (Spanish Registry of Systemic Lupus Erythematosus of the Spanish Society of Rheumatology). We included all patients diagnosed with SLE since the year 2000 and recorded sociodemographic, clinical and serological variables, comorbidities and treatments, as well as indicators of disease activity, damage and severity. The characteristics of the deceased patients were compared with those of the survivors, and variables with clinical significance or statistical significance were grouped into multivariate models to determine which ones were independently associated with the outcome of the disease. Results: A total of 2004 patients were included, 88.6% female, the mean age at diagnosis was 38.3 (± 15.3) years, with a mean delay in diagnosis of 28.9 (± 52.6) months. Up to 2.84% of the individuals had died. The leading cause of death was SLE activity (n=16), followed by infections (n=14), vascular events (n=7) and cancer (n=6). The mean age of death was 54.68 (± 20.13) years, and neither age, sex nor delay in diagnosis was independently associated with mortality. The presence of nephritis, depression, severe infections, organ damage (SLICC/ACR DI) or disease activity (SLEDAI), as well as the use of cyclophosphamide, rituximab or high doses of corticosteroids, were predictors of mortality in our cohort. Antimalarial treatment and skin manifestations were linked to improved survival. Conclusion: In the RELESSER cohort, clinical factors, co-morbidities, as well as therapeutic attitudes were associated with a significant increase in mortality in SLE. Interestingly, depression was independently associated to mortality. The activity of the disease and infections continue to be the main causes of death at the beginning of the 21st century amongst our patients. Disclosure of Interests: Clara Moriano: None declared, Jaime Calvo Grant/research support from: Lilly, UCB, Consultant of: Abbvie, Jansen, Celgene, Iñigo Rua-Figueroa: None declared, Elvira Diez Alvarez: None declared, Cristina Bermúdez: None declared, Francisco J López-Longo Grant/research support from: AbbVie and GSK, Speakers bureau: AbbVie, Actelion, Bristol Myers Squibb, GSK, MSD, Pfizer, Roche, and UCB Pharma, María Galindo-Izquierdo: None declared, Alejandro Olive: None declared, Eva Tomero Muriel: None declared, Antonio Fernandez-Nebro: None declared, Mercedes Freire González: None declared, Olaia Fernández- Berrizbeitia: None declared, Ana Pérez Gómez: None declared, Esther Uriarte Isacelaya: None declared, Carlos Marras Fernandez Cid: None declared, Carlos A. Montilla-Morales: None declared, Gregorio Santos Soler: None declared, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD, M. Rodíguez-Gómez: None declared, Paloma Vela-Casasempere: None declared, Alina Boteanu: None declared, J. Narváez: None declared, Victor Martinez Taboada: None declared, Blanca Hernández-Cruz Speakers bureau: Abbvie, Lilly, Sanofi, BMS, STADA, José Luis Andreu: None declared, José A Hernandez Beriain: None declared, Lorena Expósito: None declared, Raúl Menor-Almagro: None declared, Mónica Ibañez Barceló: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Carles Galisteo: None declared, Enrique Raya: None declared, Víctor Quevedo Vila: None declared, Tomas Vazquez Rodriguez: None declared, Jesus Ibañez: None declared, Jose M Pego-Reigosa: None declared